Measuring Work Productivity In Improving Employee Performance Based On Work Discipline - Suriadi, Suriadi; Dharmawan, Donny; Nugroho, Budi Sulistiyo; Edward, Yusuf Ronny; Judijanto, Loso (International Journal of Artificial Intelligence Research, 2024)
The purpose of the study is to analyze the role of work discipline in improving employee performance with work productivity as an intervening variable at PT. Sejahtera Mandiri of Semarang. This study uses a quantitative method using a questionnaire to collect the necessary data. The research sample consisted of 98 people obtained through a census technique. The analysis used to process the data used the Structural Equation Model (SEM) through the Partial Least Square (PLS) approach with the help of the SmartPLS ver. 3.2.9 program. The results of this study indicate that work discipline and work productivity have a positive and significant effect on employee performance. Work discipline indirectly through work productivity as an intervening variable has a significant effect on employee performance